Mapping the Endothelial Cell S-Sulfhydrome Highlights the Crucial Role of Integrin Sulfhydration in Vascular Function. Issue 9 (14th December 2020) - Bibli, Sofia-Iris; Hu, Jiong; Looso, Mario; Weigert, Andreas; Ratiu, Corina; Wittig, Janina; Drekolia, Maria Kyriaki; Tombor, Lukas; Randriamboavonjy, Voahanginirina; Leisegang, Matthias S.; Goymann, Philipp; Delgado Lagos, Fredy; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: In vascular endothelial cells, cysteine metabolism by the cystathionine γ lyase (CSE), generates hydrogen sulfide–related sulfane sulfur compounds (H2 Sn ), that exert their biological actions via cysteine S -sulfhydration of target proteins. This study set out to map the " S -sulfhydrome" (ie, the spectrum of proteins targeted by H2 Sn ) in human endothelial cells. Methods: Liquid chromatography with tandem mass spectrometry was used to identify S -sulfhydrated cysteines in endothelial cell proteins and β3 integrin intraprotein disulfide bond rearrangement. Functional studies included endothelial cell adhesion, shear stress–induced cell alignment, blood pressure measurements, and flow-induced vasodilatation in endothelial cell–specific CSE knockout mice and in a small collective of patients with endothelial dysfunction. Results: Three paired sample sets were compared: (1) native human endothelial cells isolated from plaque-free mesenteric arteries (CSE activity high) and plaque-containing carotid arteries (CSE activity low); (2) cultured human endothelial cells kept under static conditions or exposed to fluid shear stress to decrease CSE expression; and (3) cultured endothelial cells exposed to shear stress to decrease CSE expression and treated with solvent or the slow-releasing H2 Sn donor, SG1002. The endothelial cell " S -sulfhydrome" consisted of 3446 individual cysteine residues in 1591 proteins. The most altered family of proteins were the integrins and focusing on β3 integrin in detail we found that S -sulfhydration affected intraprotein disulfide bond formation and was required for the maintenance of an extended-open conformation of the β leg. β3 integrin S -sulfhydration was required for endothelial cell mechanotransduction in vitro as well as flow-induced dilatation in murine mesenteric arteries. In cultured cells, the loss of S -sulfhydration impaired interactions between β3 integrin and Gα13 (guanine nucleotide-binding protein subunit α 13), resulting in the constitutive activation of RhoA (ras homolog family member A) and impaired flow-induced endothelial cell realignment. In humans with atherosclerosis, endothelial function correlated with low H2 Sn generation, impaired flow-induced dilatation, and failure to detect β3 integrin S -sulfhydration, all of which were rescued after the administration of an H2 Sn supplement. Conclusions: Vascular disease is associated with marked changes in the S -sulfhydration of endothelial cell proteins involved in mediating responses to flow. Short-term H2 Sn supplementation improved vascular reactivity in humans highlighting the potential of interfering with this pathway to treat vascular disease.